Association between Patientâs Basic Characteristic and Clark Level in Cutaneous Malignant Melanoma - Rahmalaelani, Egie; Usman, Hermin Aminah; Agusni, Jono Hadi (Althea Medical Journal, 2017)
Background: Malignant melanoma isÂ  a cancer that begins in the melanocytes. Melanoma is commonly happened on older people, male and located on sun exposure body area, such as face, neck and lower limb. Melanoma cases occur less than 5% of skin cancer but cause a majority of skin cancer deaths because melanoma has an aggressive behavior. Age, sex, location of lesion, and type of melanoma influences the melanoma invasion. The cutaneous melanoma invasion could be assessed with the Clark level. This study is aimed to determine the association between patientâs basic characteristic and Clark level in cutaneous malignant melanoma.Methods: This study used cross sectional analytic design. The medical records and histopathology slide from the Department of Anatomic Pathology Dr. Hasan Sadikin General Hospital from 2008â2012 took as a sample. Forty one data were meet the inclusion criteria.Â  Furthermore, those data were analyzed using chi-square test.Result: Overall, patientâs characteristic in this study, commonly occurred on female (66%), 50â59 years group age (35%), non-cephalic/acral location (71%), and the level V in Clark level (73%). Location of lesion showed an association with Clark level (p=0.023), whereas, age and sex was not significant (p=0.679 and p=0.389).Conclusions: There is an association between location of lesion and Clark level [AMJ.2017;4(1):25â9]DOI:Â 10.15850/amj.v4n1.1015Â